ANALYSIS OF PROMOTIONAL EFFECTIVENESS ON INSTAGRAM-CENTRIC ACCOUNTS - Angelia Lauren Handoko; Maria Yosephine Dwi Hayu Agustini (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
This study investigates the effectiveness of promotional activities on McDonald's Indonesia's centralized Instagram account. Despite Instagram's potential as a cost-effective and engaging promotional platform, centralized accounts may face challenges in maintaining interaction and responsiveness. Utilizing a qualitative research design, data was collected through the documentation of consumer comments on McDonald's promotional posts. These comments were analyzed using the EPIC model, which evaluates Empathy, Persuasion, Impact, and Communication elements in consumer feedback. Results indicate that McDonald's promotional activities successfully create strong emotional connections, positively influence consumer attitudes, and enhance brand perception. Consumers showed increased engagement, knowledge, and satisfaction with the brand. However, the study also identified limitations in responsiveness due to the centralized nature of the Instagram account. The findings underscore the need for improved interaction and message management to optimize promotional effectiveness. This research highlights the importance of balancing centralized content management with responsive communication strategies to strengthen consumer relationships and brand loyalty.